2019
DOI: 10.3390/jcm8091289
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Joint Infection Caused by Gram-Positive Versus Gram-Negative Bacteria: Lipopolysaccharide, but not Lipoteichoic Acid, Exerts Adverse Osteoclast-Mediated Effects on the Bone

Abstract: Periprosthetic joint infection (PJI)—the most common cause of knee arthroplasty failure—may result from Gram-positive (GP) or Gram-negative (GN) bacterial infections. The question as to whether PJI due to GP or GN bacteria can lead to different rates of aseptic loosening after reimplantation remains open. We have investigated this issue through a retrospective review of clinical records obtained from 320 patients with bacterial PJI. The results revealed that, compared with GP infections, GN infections were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…In addition, the current two-stage revision for PJI that involves debridement and an antibiotic-impregnated polymethylmethacrylate spacer has exhibited outcome failure [34,35]. We previously published a retrospective review of clinical records obtained from 320 patients with bacterial PJI [20]. The study demonstrated that GN bacterial infections were associated with an increased risk of aseptic loosening as compared with GP bacterial infections [20].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the current two-stage revision for PJI that involves debridement and an antibiotic-impregnated polymethylmethacrylate spacer has exhibited outcome failure [34,35]. We previously published a retrospective review of clinical records obtained from 320 patients with bacterial PJI [20]. The study demonstrated that GN bacterial infections were associated with an increased risk of aseptic loosening as compared with GP bacterial infections [20].…”
Section: Discussionmentioning
confidence: 99%
“…We previously published a retrospective review of clinical records obtained from 320 patients with bacterial PJI [20]. The study demonstrated that GN bacterial infections were associated with an increased risk of aseptic loosening as compared with GP bacterial infections [20]. Moreover, LPS-treated mice had reduced body weight, higher serum osteocalcin levels, and more osteoclasts [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations